Case Report: Temporary supratrochanteric plating for the management of subtrochanteric femoral fracture in an immature dog - Bae, Hojung; Yoon, Jongpil; Jeon, Youngjin; Lee, Haebeom; Jeong, Jaemin (Frontiers in Veterinary Science, 2025)
This case report describes the successful management of a subtrochanteric femoral fracture in a 2-month-old dog using temporary supratrochanteric plate fixation, performed prior to the development of the greater trochanter apophysis. A tibial plateau leveling osteotomy plate was applied to the proximolateral femur and subsequently removed following radiographic evidence of bridging callus formation. At the 21-month follow-up, the dog exhibited normal limb function, symmetrical femoral length, and appropriate development of the greater trochanter. Although a mild procurvatum deformity was noted, no clinical signs or range of motion deficits were observed. These findings support the use of temporary fixation across the trochanteric region as a feasible treatment strategy for immature subtrochanteric femoral fractures when performed prior to apophyseal development.